Prevalence and associated variables to alcohol abuse in public transportation drivers in Lima, Peru - Ruiz-Grosso, Paulo (2025)
Objective: To analyze the association of sociodemographic, occupational, and mental health variables with alcohol use disorders (AUD) among public transportation drivers in Lima, Peru. Materials and methods: A secondary analysis of a cross-sectional survey was conducted with data from 278 bus drivers (BD) and 227 mototaxi drivers (MTD) from 25 transportation companies selected through snowball sampling. AUD was assessed using the CAGE questionnaire (cutoffs ≥1 and ≥2 for AUD-1 and AUD-2, respectively). Sociodemographic, occupational, and mental health variables, including depression, anxiety, and burnout, were also recorded. Prevalence and associated factors were analyzed using logistic regression models. Results: Prevalence rates for AUD-1 and AUD-2 were 74.4% and 58.4%, respectively. Significant variation was observed between BD companies (p = 0.001), but not between BD and MTD. For AUD-1, male gender (OR = 7.8; 95%CI: 1.8-34.1), being a BD (OR = 0.27; 95%CI: 0.13-0.56), and being divorced (OR = 9.5; 95%CI: 1.14-79.03) were significant factors. For AUD-2, male gender (OR = 5.49; 95%CI: 1.50-20.07), being a BD (OR = 0.52; 95%CI: 0.30-0.92), and the depersonalization subscale score (OR = 1.05; 95%CI: 1.005-1.10) were associated. Conclusions: AUD is prevalent among public transportation drivers in Lima. Male gender and being a mototaxi driver seem to increase AUD risk, while depersonalization is linked to alcohol dependence severity.